2021
DOI: 10.3389/fpsyg.2021.580565
|View full text |Cite
|
Sign up to set email alerts
|

“Finding an Emotional Face” Revisited: Differences in Own-Age Bias and the Happiness Superiority Effect in Children and Young Adults

Abstract: People seem to differ in their visual search performance involving emotionally expressive faces when these expressions are seen on faces of others close to their age (peers) compared to faces of non-peers, known as the own-age bias (OAB). This study sought to compare search advantages in angry and happy faces detected on faces of adults and children on a pool of children (N = 77, mean age = 5.57) and adults (N = 68, mean age = 21.48). The goals of this study were to (1) examine the developmental trajectory of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(7 citation statements)
references
References 85 publications
1
6
0
Order By: Relevance
“…As in these previous studies, group differences were also found between happy and sad conditions in the current study. Previous studies reported that PCA occurs in both healthy adults and children [ 50 , 51 , 52 ], and this finding was replicated in the present study. Positive facial expressions may have an advantage in visual processing because of the importance of positive expressions in emotion regulation and social relationship formation, and because they occur at a higher frequency than negative facial expressions.…”
Section: Discussionsupporting
confidence: 90%
“…As in these previous studies, group differences were also found between happy and sad conditions in the current study. Previous studies reported that PCA occurs in both healthy adults and children [ 50 , 51 , 52 ], and this finding was replicated in the present study. Positive facial expressions may have an advantage in visual processing because of the importance of positive expressions in emotion regulation and social relationship formation, and because they occur at a higher frequency than negative facial expressions.…”
Section: Discussionsupporting
confidence: 90%
“…neutral expression is important because it allows for a dichotomous analysis of whether a face contains emotion or not. Second, this study did not take into account the own-age bias, in which face recognition is typically superior for own-age faces compared with other-age faces [44]. In this study, all participants were shown the same photographs of young people 20-30 years of age.…”
Section: Plos Onementioning
confidence: 99%
“…Interestingly, for detection speed there is no own-age bias in children, nor for happy faces in adult participants. However, this bias was observed for angry and fearful faces in adult participants [37]. Although this implies that processes underlying labeling of expressions are already affected by a bias towards specific expressions or stimulus age, it is important to realize that the biases in detection concern processing speed rather than the accuracy that was the focus of the current task, and that working memory likely plays a minimal role in labeling when stimulus and labels are presented at the same time.…”
Section: Plos Onementioning
confidence: 88%
“…Indeed, working memory for emotional faces already has a response bias to happy faces [34]. Moreover, multiple studies have shown that specific emotional faces are detected faster than others when presented amongst neutral faces, although there is a debate on whether this so-called superiority effect is mostly present for happy or angry faces [35][36][37]. Interestingly, for detection speed there is no own-age bias in children, nor for happy faces in adult participants.…”
Section: Plos Onementioning
confidence: 99%